The accident - Carrick, Carol; Carrick, Donald (New York : Seabury Press, 1976)
After his dog is hit by a truck and killed, Christopher must deal with his own feelings of depression and guilt.
"A Clarion book.".
Booklist.
Kirkus Review.
Reference and Research Book News.
3.3
K-3
Keywords: Dogs -- Fiction; Death -- Fiction; Dogs -- Fiction; Death -- Fiction; Death -- Fiction; Dogs -- Fiction